The Factors Effects on Quality Management System in Construction - Mohammed Resan Kareem; Prof. Dr. Gozde Ulutagay (International Journal of Engineering and Management Research, 2022)
Construction's requirement for quality management is now widely acknowledged. Implementing the quality standard elements in the field will be fraught with practical obstacles. And the majority of staff are enthusiastic. They are participating in this procedure without benefit. Appropriate method or standard for fixing the standards, Quality assurance, quality control, and quality planning are used to define the quality management system (QMS). It is vital for the construction industry to certify that projects will be completed successfully and without hiccups. Highest quality, exact quantity, and lowest possible price. This essay intends to create a critical and constructive critique by examining five published works Publications pertaining to QMS in the building industry The paper will investigate the variables influencing the deployment of quality management systems in building projects. Paper objectives were to identify crucial elements impacting QMS application, advantages that stimulate QMS implementation, and prerequisites or needs for QMS implementation. The study's purpose was to examine the successful major issues in the Quality Management System.